2012
DOI: 10.2337/dc11-1577
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling of Fatty Acid and Amino Acid Metabolism in Youth With Obesity and Type 2 Diabetes

Abstract: OBJECTIVEWe compared acylcarnitine (AcylCN) species, common amino acid and fat oxidation (FOX) byproducts, and plasma amino acids in normal weight (NW; n = 39), obese (OB; n = 64), and type 2 diabetic (n = 17) adolescents.RESEARCH DESIGN AND METHODSFasting plasma was analyzed by tandem mass spectrometry, body composition by dual energy X-ray absorptiometry and computed tomography, and total-body lipolysis and substrate oxidation by [2H5]glycerol and indirect calorimetry, respectively. In vivo insulin sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
196
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(208 citation statements)
references
References 36 publications
(54 reference statements)
6
196
5
1
Order By: Relevance
“…Further, in a previous study we found that a lower serum histidine level in obese women, compared with non-obese healthy women, was associated with inflammation and oxidative stress [9]. Moreover, another recent study also found that the histidine level was lower in young obese individuals and in individuals with type 2 diabetes and was correlated with insulin sensitivity [10].…”
Section: Introductionmentioning
confidence: 83%
“…Further, in a previous study we found that a lower serum histidine level in obese women, compared with non-obese healthy women, was associated with inflammation and oxidative stress [9]. Moreover, another recent study also found that the histidine level was lower in young obese individuals and in individuals with type 2 diabetes and was correlated with insulin sensitivity [10].…”
Section: Introductionmentioning
confidence: 83%
“…A family of aldo-keto reductase enzymes can use a wide variety of carbonyl compounds as their substrates and reduce these to their respective sugar alcohols (polyols) using NADPH ( Figure 2). Animal studies indicate an early increase in metabolic flow via all these pathways and suggest their potential damaging roles (35). Hyperglycemia also increases the non-enzymatic reaction of glucose and other glycating compounds derived both from glucose and from increased fatty acid oxidation, which generates advanced glycation end products in complication-prone cell types, including kidney cells (36).…”
Section: Figurementioning
confidence: 99%
“…Papers finally included n = 13 Zeng et al [19] Pietiläinen et al [41] Oberbach et al [9] Newgard et al [12] Karlsson et al [39] Wahl et al [11] Mihalik et al [21] Kim et al [14] McCormack et al [20] Okada et al [35] Warensjö et al [38] Moore et al [13] Study design …”
Section: Acylcarnitinesmentioning
confidence: 99%